Some Reflections on Philosophy, Democracy, and Religion - Carlos Fraenkel (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2007)
What is the use of philosophy, especially in the present era? This article seeks to convince that philosophy is highly beneficial for human life. Philosophy does not merely speculate about abstract matters, as many people perceive, but since the time of Socrates, it has developed to be grounded and practical. Socrates brought philosophy into the public sphere, not confined to seminar rooms. From here, philosophical discussions emerged that touched various aspects of human life. Since then, philosophy has delved into radical and profound discussions on a wide range of topics, including democracy and religion.